Cancer cells impact the microrheology of endothelial cells during physical contact or through paracrine signalling - Georgia M. Kefala; Daria Tsvirkun; Valérie M. Laurent; Claude Verdier (Scientific Reports)
Abstract During the process of metastasis, cancer cells transmigrate through the endothelial barrier of the vascular walls. Cancer cells interact with the endothelial cells, leading to changes of their mechanical properties. While this interaction has been extensively studied from the perspective of cancer cells (CCs), the mechanical properties of the endothelium remain underexplored, even though they may play a crucial role in regulating this process. In this study, we used a microrheology AFM-based approach to demonstrate that the properties of endothelial cells (ECs) are altered when cultured either in CC-conditioned medium or in direct contact with cancer cells. We found that the viscoelasticity of ECs decreased when cultured in diluted CC-conditioned medium. Furthermore, ECs in direct contact with a cancer cell at short times (less than 30 min) also showed significantly lower stiffness and viscoelastic moduli. In parallel, we observed a reduction in the quantity of actin fibers and actin clusters within the EC cytoskeleton, resulting in a less structured network that may facilitate CC transmigration. Overall, our findings indicated that the rheological properties of ECs can be altered either directly through physical contact with CCs or indirectly via CC-secreted substances. This suggests that the endothelium actively responds to the presence of cancer cells, rather than serving only as a passive barrier.